Correlation between the duration of fixed orthodontic treatment and psychosocial impact among medical and dental students: Study cross-sectional - Suyitno, Clarissa Jilan Sauzan Salmamuntai; Rokhim, Saiful; Irsal, Imran (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
ABSTRACTIntroduction: One of the most common oral health problems is malocclusion. This condition can affect psychosocial well-being. Malocclusion can be managed through fixed orthodontic treatment, which corrects dental irregularities and improves dental aesthetics and the patient’s psychosocial well-being. This study aimed to analyze the correlation between the duration of fixed orthodontic treatment and psychosocial impact among medical and dental students. Methods: This study used a cross-sectional design with purposive sampling. The sample consisted of 68 students who were undergoing fixed orthodontic treatment. Primary data were collected using the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). Bivariate analysis was performed using non-parametric statistical tests, namely Spearman’s rho and Mann-Whitney test. Results: A total of 68 participants were included in this study, with 44.1% using fixed orthodontic appliances for < 1 year. The mean psychosocial impact score was 41.26 ± 17.09, which was classified as low. A negative correlation was found between the duration of fixed orthodontic treatment and psychosocial impact among medical and dental students (p=0.001, r=-0.4). Conclusions: The longer the duration of fixed orthodontic treatment, the lower psychosocial impact experienced by patients.KEY WORDS: fixed orthodontic appliances, psychosocial impact, self-confidence, dental aesthetics, studentsKorelasi durasi perawatan ortodonti cekat terhadap dampak psikososial mahasiswa kedokteran dan kedokteran gigi: Studi cross-sectionalABSTRAKPendahuluan: Salah satu permasalahan kesehatan gigi dan mulut yang paling banyak ditemui adalah maloklusi. Kondisi ini dapat memengaruhi dampak psikososial. Penanganan maloklusi dapat dilakukan melalui perawatan ortodonti cekat yang dapat mengoreksi ketidakteraturan gigi dan sekaligus meningkatkan estetika serta meningkatkan kesejahteraan psikososial pasien. Penelitian ini bertujuan untuk menganalisis korelasi antara durasi perawatan ortodonti cekat terhadap dampak psikososial pada mahasiswa kedokteran dan kedokteran gigi. Metode: Penelitian ini menggunakan desain cross-sectional dengan teknik teknik purposive sampling. Sampel penelitian terdiri atas 68 mahasiswa yang sedang menjalani perawatan ortodonti cekat. Data primer diperoleh melalui instrumen kuesioner PIDAQ. Analisis bivariat menggunakan uji statistik non parametrik berupa Spearman’s rho dan Mann-Whitney. Hasil: Total 68 sampel, sebanyak 44,1% sedang menggunakan ortodonti cekat selama < 1 tahun, skor rerata dampak psikososial sebesar 41,26 ±17,09 yang termasuk dalam kategori rendah. Terdapat korelasi negatif antara perawatan ortodonti cekat terhadap dampak psikososial pada mahasiswa kedokteran dan kedokteran gigi (p=0,001 r=-0,4) Simpulan: Semakin lama durasi perawatan ortodonti cekat, maka semakin rendah dampak psikososial yang dirasakan. KATA KUNCI: ortodonti cekat, dampak psikososial, kepercayaan diri, estetika gigi, mahasiswa